2023
DOI: 10.1177/11206721231159694
|View full text |Cite
|
Sign up to set email alerts
|

Topical netarsudil for treatment of glaucoma with elevated episcleral venous pressure: A pilot investigation in sturge-weber syndrome

Abstract: Purpose Topical netarsudil 0.02% may reduce intraocular pressure (IOP) by decreasing episcleral venous pressure (EVP), which carries theoretical utility for glaucoma associated with elevated EVP. A role for netarsudil in patients with elevated EVP is evaluated in a pilot investigation using a cohort of individuals with Sturge-Weber syndrome (SWS). Methods Retrospective study of patients with SWS and glaucoma who were treated with netarsudil. Five patients (six eyes) were identified. Data collected included dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Preliminary evidence suggests that netarsudil can provide additional IOP-lowering effects in patients with uveitic glaucoma on maximal tolerated medical therapy [59]. Netarsudil has also been shown to be effective in a cohort of patients with Sturge-Weber Syndrome on maximal medical therapy by reducing EVP [60], and it demonstrated similar efficacy to latanoprostene bunod when used as adjunct therapy in patients on maximal therapy for POAG [61]. The efficacy of netarsudil has also been compared to ripasudil in the J-ROCKET study and demonstrated a stronger IOP-lowering effect [62].…”
Section: Netarsudil In Glaucomamentioning
confidence: 99%
“…Preliminary evidence suggests that netarsudil can provide additional IOP-lowering effects in patients with uveitic glaucoma on maximal tolerated medical therapy [59]. Netarsudil has also been shown to be effective in a cohort of patients with Sturge-Weber Syndrome on maximal medical therapy by reducing EVP [60], and it demonstrated similar efficacy to latanoprostene bunod when used as adjunct therapy in patients on maximal therapy for POAG [61]. The efficacy of netarsudil has also been compared to ripasudil in the J-ROCKET study and demonstrated a stronger IOP-lowering effect [62].…”
Section: Netarsudil In Glaucomamentioning
confidence: 99%